What Drives Consumers to Buy Online? A Study on Exploring Online Consumer Behavior - Kuşçu, Aslı; YOZGAT, UĞUR (Kafkas Üniversitesi, İktisadi ve İdari Bilimler Fakültesi, 2019)
This research contributes to the understanding of online shopping by investigating influential factors on consumers’ online search andpurchase intentions. Given the fact that previous studies mostly concentrated on the utilitarian and hedonic aspects and yet still provided mixed results, a comprehensive theoretical framework is developed thatcombines current research on utilitarian and hedonic values and factors that lead to those values while also emphasizing the importance of the perceived congruence between the consumer and online shoppingand linking it to both hedonic values and to online search and purchase intentions. The structural model design tested with 358 online consumers enables the researchers to evaluate all factors in a holistic fashionand our results demonstrate the importance of making use of the properties of the medium while also providing the consumer with a shopping experience that is rich in information, sensory stimulation, and also in selfexpression. Results are consistent across demographics and product categories.

Bu çalışma müşterilerin elektronik ortamda arama ve satın alma niyetlerine etki eden faktörleri inceleyerek literatüre katkı sağlamayı amaçlamaktadır. Daha önceki çalışmalarda çoğunlukla faydacı ve hedonic yararlara yoğunlaşılması, buna rağmen çelişkili sonuçlar elde edilmesi sebebiyle bu çalışmada literatürde kullanılmış olan bu faydalara ek olarak müşteri ve elektronik satınlama arasında yaşanan imaj açısından uyumun eklenmesi ile geniş açılı bir teorik model oluşturulmuştur. Oluşturulan yapısal eşitlik modeli 358 adet elektronik müşterinin cevapları doğrultusunda test edilmiş ve sonuçlar elektronik ortamın özelliklerinin ve müşteriye sunulan bilgi, duygular ve kendini ifade etme açısından yoğun satınalma deneyiminin elektronik ortamda arama ve satın alma niyetlerine etkisi olduğunu göstermiştir. Sonuçlar farklı ürün kategorileri ve demografilerde farklılık göstermemektedir.
Müşteriler Neden Elektronik Ortamda Satın Alıyor? Elektronik Satınalma Üzerine Bir Çalışma
Keywords: Online Shopping; Hedonic Motivation; Utilitarian Motivation; Self-concept Conguity